Microwave-assisted facile synthesis and crystal structure of cis-9,10,11,15-tetrahydro-9,10[3′,4′]-furanoanthracene-12,14-dione - Weerachai Phutdhawong (2018)
A facile synthesis and crystal structure of cis -9,10,11,15-tetrahydro-9, 10[3′,4′]-furanoanthracene-12,14-dione from the reaction of anthracene and maleic anhydride in xylene in a short time and high yield using a modified commercial domestic microwave oven is reported. Copyright © Taylor & Francis Group, LLC.